Literal Translation using Google Translate in Translating the Text from French to English in Digital Tourism Brochure “Bienvenue À Paris” - Rila Hilma (Binus Business Review, 2011)
Translation is basically change of form. The form from which the translation is made will be called the source language and the form into which it is to be changed will be called the receptor language. Translation consists of transferring the meaning of the source language into the receptor language. Translating is not an easy job to do because many things to be considered to do this activity because translation means determining the meaning of a text, then reconstructing this same meaning using the appropriate structure and form in the receptor language. Translation is basically divided by two types of translation, one is literal and the other is idiomatic. Literal translation is really strict to the structure and form then often can not well express the true meaning of source language. Idiomatic translation makes every effort to communicate the meaning of the source language text in the natural forms of the receptor language. Then the most popular translation machine, Google Translate, in this study shows the results of translation which remain odd, unnatural, and nonsensical because the unsuccessful of message delivery, which is notably the typically error of literal translation.